2019
DOI: 10.1002/cbin.11083
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐1204 promotes cell proliferation by regulating PITX1 in non‐small‐cell lung cancer

Abstract: MicroRNA‐1204 (miR‐1204), a member of the PVT1 region, may improve B cell differentiation and metastasis in breast cancer. However, the role of miR‐1204 in non‐small‐cell lung cancer (NSCLC) and its mechanism remain unclear. The GEO public database was first employed to find differentially expressed genes. The expression level of miR‐1204 in patient tissues and NSCLC cell lines was determined using qRT‐PCR. Cell proliferation assays were performed to investigate the impact of miR‐1204 on cell growth. Bioinform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Both PVT1 and the well-known protein-coding gene MYC are co-located on the 8q24 chromosomal region, known as the gene desert, which contains a large number of risk alleles that are implicated in cancer [ 11 , 12 ]. PVT1 produces a wide variety of spliced non-coding RNAs, as well as a cluster of six annotated microRNAs: miR-1204, miR-1205, miR-1206, miR-1207-5p, miR-1207-3p, and miR-1208 [ 13 ], which can promote tumor proliferation [ 14 , 15 ], and the resistance of chemotherapy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both PVT1 and the well-known protein-coding gene MYC are co-located on the 8q24 chromosomal region, known as the gene desert, which contains a large number of risk alleles that are implicated in cancer [ 11 , 12 ]. PVT1 produces a wide variety of spliced non-coding RNAs, as well as a cluster of six annotated microRNAs: miR-1204, miR-1205, miR-1206, miR-1207-5p, miR-1207-3p, and miR-1208 [ 13 ], which can promote tumor proliferation [ 14 , 15 ], and the resistance of chemotherapy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR-1204 is a member of the PVT1 region. Recent studies have found that miR-1204 may improve B cell differentiation and metastasis in breast cancer and can target PITX1 in non-small cell lung cancer, which may be a poor prognostic factor and a potential therapeutic target for NSCLC [26]. We used three miRNA target prediction databases (miRanda, TargetScan, and miRWalk) to determine the target gene of miR-1204.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of the apoptosis play a significant role in the survival of abnormal cells and tumorigenesis [28,29]. Cell apoptosis is characterized by chromatin concentration, DNA fragmentation, membrane foaming, and/or apoptotic bodies [25][26][27][28][29][30]. In our study, Annexin V FITC analysis of flow cytometry and in vitro Hochest 33258 staining analysis indicated that the apoptosis rate of A549 and SPC cells in miR-1204 overexpression group was increased, while the apoptosis rate was found to have decreased in the miR-1204 inhibited group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-1204 facilitates the development of hepatocellular carcinoma by stimulating MAPK and c-JUN/AP1 pathway via targeting ZNF418 [26]. MiR-1204 induces the proliferation of non-smallcell lung cancer cells through modulating PITX1 expression [27]. However, the specific role of miR-1204 in GBM remains unclear, thus arousing our interest in exploring whether and how miR-1204 regulates the biological process in GBM cells, including cell proliferation and cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%